Virtual reality and gamification in education: a systematic review - Lampropoulos, Georgios; Kinshuk (Educational technology research and development, 2024)
This study aims to analyze the use of virtual reality and gamification in education by examining the existing literature. In addition to virtual reality, this study focuses on gamified virtual reality learning environments which refer to virtual reality learning environments that integrate gamification elements and mechanisms. Based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, a systematic literature review was carried out. No limitations were set regarding educational level, type of study, subject, and publication year. The related articles were retrieved from 5 databases (ERIC, Google Scholar, IEEE, SCOPUS, and Web of Science). A total of 112 articles were included, 16 research questions were explored, and a thematic analysis was conducted. To evaluate the quality of the articles included, the Mixed Methods Appraisal Tool (MMAT) was used. According to the findings, gamification and virtual reality support several pedagogical theories and approaches. Their adoption to and integration into education can enrich and transform traditional teaching and learning and were assessed positively by students and teachers. Gamification elements significantly affected students’ achievements. In comparison to traditional learning environments, gamified virtual reality learning environments were more motivating, engaging, and interactive and offered more opportunities for personalized and collaborative learning. Through the realistic and interactive experiences offered, students’ immersion and social presence can be enhanced, knowledge acquisition can be improved, and material comprehension can be facilitated. Positive changes in student attitude, behavior, and mentality as well as improved cognitive, physical, and social–emotional development were observed. When using learning environments that integrate both virtual reality and gamification, students’ learning outcomes, motivation, engagement, and self-efficacy were increased. Additionally, students’ academic performance, active involvement, and satisfaction were improved. Students’ curiosity, imagination, focus, and interest were enhanced and their skills and competences were developed. Finally, gamified virtual reality emerged as an effective educational tool that can improve learning at all educational levels, subjects, and contexts.